Kajian tentang Lem Bulu Mata sebagai Kosmetik untuk Koreksi Mata Menurun dalam Tata Rias Wajah Geriatri - Dewi, Fadhilah Nirwana; Puspitorini, Arita (Journal of Beauty and Cosmetology (JBC), 2020)
Geriatric make up is an advanced face makeup for elderly women, Decreasing eyes usually owned by the elderly women who want to incurs correction on the part of eyelid usually for declining eye correction many use a scotch tape for lifting eyelids, but the function of scotch tape has many shortages, for example, the strong recklessness and to sharp for the eyelid when applied to the eyelid, so it requires more durable cosmetics to hold the eyelids so that the eyelid does not fall one of the solutions made to address those problems by using adhesive cosmetics that is eyelash glue because it has a strong, durable recklessness.  The use of eyelash glue itself is widely used instead of scotch tape because its use is more efficient and cheap it has strong adhesiveness.  The purpose of doing this research is to describe the result of eyelash glue for correcting eye decrease. The method of data collection used in literature research. This research concluded that the function of the eyelash glue could replace the scotch tape for eye correction on geriatric makeup because it has good inward and absorbent power for the eyelid. Keywords: Geriatric makeup, eyelash glue